The Synthesis and Characterization of N,N?-[4,4?-{Ethane-1,2-di-yl-bis(oxy)bis(4,1-phenylene)}bis(N?-hydroxy)-2-(hydroxyimino)acetimidamide], (LH4) and Its Binuclear Complexes - Duman, S.; Sekerci, M. (Polish Chemical Soc, 2009)
A novel vic-dioxime ligand (LH4) and its transition metal complexes with Cu(ACO)(2)center dot H2O, Ni(AcO)(2) 4H(2)O, Co(ACO)(2) 4H(2)O and Cd(AcO)(2) metal salts were synthesized 1,2-Bis(p-aminophenoxy)ethane reacted with anti-chloroglyoxime to give N,N'-[4,4'- {ethane-1,2-di-yl-bis(oxy)bis(4,1-phenylcne)} bis(N'-hydroxy)-2-(hydroxyimino)acetimidamide] (LH4) ligand. Ligand forms binuclear complexes [(LH3)(2)M-2(ACO)(2)] nH(2)O with a 2:2 metal to ligand ratio, where M = Cu(II), Ni(II) and Cd(II), n = 2, 2 and 1, respectively. LH4 forms also binuclear Co(II) complex [(LH4)(2)Co-2(ACO)(4)(H2O)(2)]center dot 2H(2)O with a metal to ligand ratio of 2:2. The Ni(II) and Cd(II) complexes are proposed to be tetrahedral while the Cu(II) and Co(II) complexes should be octahedral. Structural assignments are supported by a combination of elemental analyses, UV-Vis, IR and H-1-NMR spectra, magnetic measurements and TGA and DTA techniques
Keywords: vic-oxime; transition metal complexes